The Implementation of Balance Score Card for Performance Measurement in Small and Medium Enterprises: Evidence from Malaysian Health Care Services - Suprapto, Budi; Abdul Wahab, Hasnida; Jatmiko Wibowo, Alexander (School of Business and Management Institut Teknologi Bandung, 2009)
The needs for SMEs to measure their performance is to improve their service to customers, employees, societies and stakeholders. The purpose of the study was to investigate the implementation of Balance Score Card as the performance measurement system in SMEs. In this study, 1000 mailed questionnaires were sent to health care services in Malaysia. Out of this, only 105 responded and data collected were analyzed. Using factor analysis with varimax rotation technique, the study found four factors with eigenvalue value more than 1.0. Those factors that explained total variance of 69.346 percent, indicated the four components of BSC implemented by SMEs in Malaysian Health Care Services. Those components are as follows: learning and growth, mission and vision, customer and internal business perspective.Key words: Balance Score Card, Performance Measurement, Small and Medium Enterprise